Prevalence Of Antimicrobial Resistance In Uropathogens And Determining Empirical Therapy For Urinary Tract Infections - VAKILWALA.M; RATNA TRIVEDI (International Journal of Pharma and Bio Sciences, 2012)
Analyzing antibiotic susceptibility pattern of Uropathogens helps to overcome the therapeutic difficulties created by the emerging antimicrobial resistant bacteria and guides in choosing appropriate empirical therapy. The aim of the study is to understand the susceptibility patterns of the uropathogens which assists in choosing the empirical therapy for UTI. Midstream urine samples were collected cultured and subjected to microscopical and appropriate biochemical tests for proper identification. Antimicrobial sensitivity tests were carried out by disc diffusion technique using Muller Hinton Agar. High level resistance is seen to Cotrimoxazole, Ciprofloxacin, Ceftazidime and Cefixime. Amikacin was found to be more effective against the isolates. Most of the isolates were sensitive to ceftriaxone sulbactam. From our study, Amikacin is recommended Urinary tract Infections as Empirical treatment.